Co-metabolic biodegradation of chlorinated ethene in an oxygen- and ethane-based membrane biofilm reactor - Zifang Chi; Xinyang Liu; Huai Li; Shen Liang; Yi-Hao Luo; Chen Zhou; Bruce E. Rittmann (Science of The Total Environment, 2023)

Moderate altitude exposure impacts host fasting blood glucose and serum metabolome by regulation of the intestinal flora - Dan Liu; Xiaoyan Gao; Xiaoran Huang; Yanqun Fan; Yu-E Wang; Yuelin Zhang; Xuanfu Chen; Jielu Wen; Haiwei He; Yimei Hong; Ying Liang; Yuxiao Zhang; et al. (Science of The Total Environment, 2023)

Hirsutinolide-type sesquiterpenoids with anti-prostate cancer activity from Cyanthillium cinereum - Song Ang; Chun Liu; Peng Hong; Lei Yang; Gui'e Hu; Xi Zheng; Jingwei Jin; Rihui Wu; Wing-Leung Wong; Kun Zhang; Lishe Gan; Dongli Li (Phytochemistry, 2023)

Polyguluronic acid alleviates doxorubicin-induced cardiotoxicity by suppressing Peli1-NLRP3 inflammasome-mediated pyroptosis - E Zhang; Chuangeng Shang; Mingtao Ma; Xuanfeng Zhang; Yu Liu; Shuliang Song; Xia Li (Carbohydrate Polymers, 2023)

Metabolome and Transcriptome Association Analysis Reveals the Link Between Pigmentation and Nutrition Utilization in the Juveniles of Sea Cucumber Holothuria leucospilota - Jiasheng Huang; Zixuan E; Wenjie Pan; Zhi Li; Tiehao Lin; Chunhua Ren; Peng Luo; Bo Ma; Yang Liu; Xugan Wu; Chaoqun Hu; Xiao Jiang; et al. (Marine Biotechnology, 2023)

The microbial mechanisms by which long-term heavy metal contamination affects soil organic carbon levels - Zhineng Xiao; Changqun Duan; Shiyu Li; Ji Chen; Changhui Peng; Rongxiao Che; Chang'e Liu; Yin Huang; Runran Mei; Liangliang Xu; Pengfei Luo; Yadong Yu (Chemosphere, 2023)

Dust diffusion laws during partition excavation by boom-type roadheader in a metro tunnel - Ning Liu; Xiong Wu; E Deng; Yi-Qing Ni; Wei-Chao Yang; Guo-Zhi Li (Tunnelling and Underground Space Technology, 2023)

Direct identification of total and missing OH reactivities from light-duty gasoline vehicle exhaust in China based on LP-LIF measurement - Xuehui Liu; Zibing Yuan; Qing'e Sha; Shengrong Lou; Hongli Wang; Xin Li; Junyu Zheng; Bin Yuan; Min Shao (Journal of Environmental Sciences, 2023)

The effect of long-term controlled-release urea application on the relative abundances of plant growth-promoting microorganisms - Feng Gao; Zeli Li; Yongxiang Gao; E. Gaoyang; Mingyang Li; Chuanfu Li; Yunlong Cheng; Tianjiao Zhang; Shuo Wang; Liang Wu; Zhanbo Wei; Wenkui Zheng; et al. (European Journal of Agronomy, 2023)

TFP5, a Peptide Derived from Cdk5 Activator p35, Protects Pancreatic β Cells from Glucose Toxicity - S.-Y. Liu; S.-L. Cao; H.-Y. Luo; L. Bao; J. E; B. Li; X.-M. Lan; G.-Q. Zhang; X. Bao; Y.-L. Zheng (Bulletin of Experimental Biology and Medicine, 2023)

Konjac glucomannan/low-acyl gellan gum edible coating containing thymol microcapsule regulates cell wall polysaccharides disassembly and delays postharvest softening of blueberries - Peng Huang; Jie Ding; Chunyan Liu; Hongying Li; Chenlin Wang; Yezi Lin; Dur E. Sameen; Md Alomgir Hossen; Mingrui Chen; Jing Yan; Yaowen Liu; Wen Qin (Postharvest Biology and Technology, 2023)

Research on the distribution of S species in the pressure oxidation leaching process of SrS solution - Siming Chen; Dongping Duan; Yanjiang Li; Yan Liu; E Zhou (Minerals Engineering, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Composition, function and succession of bacterial communities in the tomato rhizosphere during continuous cropping - Lv Su; Huatai Li; Jing Wang; Wenting Gao; Xia Shu; Xiting Sun; Kesu Wang; Yan Duan; Yunpeng Liu; Eiko E. Kuramae; Ruifu Zhang; Biao Shen (Biology and Fertility of Soils, 2023)

A New Machine-Learning Extracting Approach to Construct a Knowledge Base: A Case Study on Global Stromatolites over Geological Time - Xiaobo Zhang; Hao Li; Qiang Liu; Zhenhua Li; Claire E. Reymond; Min Zhang; Yuangeng Huang; Hongfei Chen; Zhong-Qiang Chen (Journal of Earth Science, 2023)

Co-generation of hydroxyl and sulfate radicals via homogeneous and heterogeneous bi-catalysis with the EO-PS-EF tri-coupling system for efficient removal of refractory organic pollutants - Wanlin Yang; Zejun Deng; Libin Liu; Kechao Zhou; Sharel P. E; Lingcong Meng; Li Ma; Qiuping Wei (Water Research, 2023)

Non-uniform dissolved oxygen distribution and high sludge concentration enhance simultaneous nitrification and denitrification in a novel air-lifting reactor for municipal wastewater treatment: A pilot-scale study - Yun Li; Shujie Liu; Lanlan Lu; Jinghou Wang; Guangrong Huang; Fuming Chen; Jian-e Zuo (Bioresource Technology, 2023)

Delays in heading and improvements in both spikelet number and spike length are associated with the Aegilops tausschii photoperiod-sensitive ppd-D1b allele - Shunzong Ning; Laibin Zhao; Shijie Li; Shengke Li; Tianqing Zang; Yu’e Liu; Hongkun Yang; Xuejiao Chen; Xue Chen; Yingjin Yi; Ming Hao; Lianquan Zhang; et al. (Cereal Research Communications, 2023)

Identification of general features in soil fungal communities modulated by phenolic acids - Lv Su; Huatai Li; Xiting Sun; Kesu Wang; Xia Shu; Wenting Gao; Yunpeng Liu; Eiko E. Kuramae; Biao Shen; Ruifu Zhang (Applied Soil Ecology, 2023)

Global mapping of urban thermal anisotropy reveals substantial potential biases for remotely sensed urban climates - Huilin Du; Wenfeng Zhan; Zihan Liu; E. Scott Krayenhoff; TC Chakraborty; Lei Zhao; Lu Jiang; Pan Dong; Long Li; Fan Huang; Shasha Wang; Yuyue Xu (Science Bulletin, 2023)

Paleoclimatic and anthropogenic impacts on the environment of Southwest China since 33 ka based on multiproxy analysis of karst depression deposits - Xing Tian; Xiaoyong Long; Shu’e Luo; Min Cao; Ji Li; Yuchuan Sun; Sibo Zeng; Ze Wu; Chuan Liu; Lidan Lei; Thomas J. Algeo; Yongjun Jiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

An efficient method to enhance recovery and detection of SARS-CoV-2 RNA in wastewater - Teresa Kumblathan; Yanming Liu; Yuanyuan Qiu; Lilly Pang; Steve E. Hrudey; X. Chris Le; Xing-Fang Li (Journal of Environmental Sciences, 2023)

Enhanced Degradation of Acid Orange 52 Using a Polyextremophilic Ascomycete in Stirred Tank Bioreactor - Qandeel Laraib; Maryam Shafique; Muhammad Ali Versiani; Khitab Gul; Uroosa Ejaz; Haji Muhammad; Sehar Afshan Naz; Drauzio E. N. Rangel; Alene Alder-Rangel; Kousar Yasmeen; Nusrat Jabeen; Jing Liu; et al. (Water, Air, & Soil Pollution, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

Metal mixture exposure and the risk for immunoglobulin A nephropathy: Evidence from weighted quantile sum regression - Shaohui Liu; Li’e Zhang; Na Luo; Mingjun Wang; Chuanqiao Tang; Jiajun Jing; Hao Chen; Qiuhua Hu; Lina Tan; Xiaoli Ma; Yunfeng Zou (Environmental Science and Pollution Research, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

Astrochronology and sedimentary noise modeling of Pliensbachian (Early Jurassic) sea-level changes, Paris Basin, France - Rui Zhang; David B. Kemp; Nicolas Thibault; Mads E. Jelby; Mingsong Li; Chunju Huang; Yu Sui; Zhixiang Wang; Dongyang Liu; Shizhen Jia (Earth and Planetary Science Letters, 2023)

Western diet unmasks transient low-level vinyl chloride-induced tumorigenesis; potential role of the (epi-)transcriptome - Silvia Liu; Liqing He; Olivia B. Bannister; Jiang Li; Regina D. Schnegelberger; Charis-Marie Vanderpuye; Andrew D. Althouse; Francisco J. Schopfer; Banrida Wahlang; Matthew C. Cave; Satdarshan P. Monga; Xiang Zhang; et al. (Toxicology and Applied Pharmacology, 2023)

Inter-regional environmental inequality under lasting pandemic exacerbated by residential response - Chunjin Li; Jintai Lin; Lulu Chen; Qi Cui; Yu Liu; Erin E. McDuffie; Mingxi Du; Hao Kong; Jingxu Wang (Science of The Total Environment, 2023)

A rapid chemometrics model for antioxidant substance mining of Chinese dwarf cherry [Cerasus humilis (Bge.) Sok.] based on polyphenol profile and antioxidant capacity of 30 germplasms - Yushi Zhang; Qingyu Cui; Chang-e Guo; Xiaobing Zhang; Shupeng Liu; Xiaoxue Wang; Jinjiang Zhao; Zihan Zhao; Weidong Li (Food Bioscience, 2023)

Long-term application of controlled-release potassium chloride increases maize yield by affecting soil bacterial ecology, enzymatic activity and nutrient supply - Zeli Li; Lixue Qiu; Tianjiao Zhang; Gaoyang E; Lili Zhang; Lingli Wang; Liang Wu; Yanfeng Wang; Yunfeng Zhang; Jun Dong; Wenjing Li; Zhiguang Liu; et al. (Field Crops Research, 2023)

Another Year of Record Heat for the Oceans - Lijing Cheng; John Abraham; Kevin E. Trenberth; John Fasullo; Tim Boyer; Michael E. Mann; Jiang Zhu; Fan Wang; Ricardo Locarnini; Yuanlong Li; Bin Zhang; Fujiang Yu; et al. (Advances in Atmospheric Sciences, 2023)
Changes in ocean heat content (OHC), salinity, and stratification provide critical indicators for changes in Earth’s energy and water cycles. These cycles have been profoundly altered due to the emission of greenhouse gasses and other anthropogenic substances by human activities, driving pervasive changes in Earth’s climate system. In 2022, the world’s oceans, as given by OHC, were again the hottest in the historical record and exceeded the previous 2021 record maximum. According to IAP/CAS data, the 0–2000 m OHC in 2022 exceeded that of 2021 by 10.9 ± 8.3 ZJ (1 Zetta Joules = 10 21 Joules); and according to NCEI/NOAA data, by 9.1 ± 8.7 ZJ. Among seven regions, four basins (the North Pacific, North Atlantic, the Mediterranean Sea, and southern oceans) recorded their highest OHC since the 1950s. The salinity-contrast index, a quantification of the “salty gets saltier—fresh gets fresher” pattern, also reached its highest level on record in 2022, implying continued amplification of the global hydrological cycle. Regional OHC and salinity changes in 2022 were dominated by a strong La Niña event. Global upper-ocean stratification continued its increasing trend and was among the top seven in 2022.

Decreasing expression of Prohibitin-2 lowers the oncogenicity of renal cell carcinoma cells by suppressing eIF4E-mediated oncogene translation via MNK inhibition - Jie Yang; Gang Li; Yue'e Huang; Ying Liu (Toxicology and Applied Pharmacology, 2023)

Machine learning and deep learning based on the small FT-MIR dataset for fine-grained sampling site recognition of boletus tomentipes - Jian-E Dong; Jieqing Li; Honggao Liu; Yuan-Zhong Wang (Food Research International, 2023)

Recent advances in the fabrication of pH-sensitive indicators films and their application for food quality evaluation - Qingying Luo; Alomgir Hossen; Dur E Sameen; Saeed Ahmed; Jianwu Dai; Suqing Li; Wen Qin; Yaowen Liu (Critical Reviews in Food Science and Nutrition, 2023)

Simple and efficient solid phase extraction based on molecularly imprinted resorcinol–formaldehyde resin nanofibers for determination of trace sulfonamides in animal-origin foods - Yuanyuan Dai; Niu Wu; Li-e Liu; Fei Yu; Yongjun Wu; Ningge Jian (Food Chemistry, 2023)

Trends in elemental Pb concentrations within atmospheric PM2.5 and associated risk to human health in major cities of China - Qian Cui; Liangzhong Li; Yaqiang Cao; Bo Yang; Lindou Liu; Xiaoyan Dong; Yu'e Cha; Hongjie Ruan; Song Tang; Qiong Wang (Environmental Pollution, 2023)

A 1000-year hydroclimate record from the Asian summer monsoon-Westerlies transition zone in the northeastern Qinghai-Tibetan Plateau - Luo Qin; Guangxin Liu; Xiangzhong Li; E. Chongyi; Jiang Li; Changrun Wu; Xin Guan; Yuan Wang (Climatic Change, 2023)

Spatio‐temporal patterns in the woodiness of flowering plants - Ao Luo; Xiaoting Xu; Yunpeng Liu; Yaoqi Li; Xiangyan Su; Yichao Li; Tong Lyu; Dimitar Dimitrov; Markku Larjavaara; Shijia Peng; Yongsheng Chen; Qinggang Wang; et al. (Global Ecology and Biogeography, 2023)
Aim Woody and herbaceous habits represent one of the most distinct contrasts among angiosperms, and the proportion of woody species in floras (i.e., “woodiness” hereafter) represents a fundamental structural element of plant diversity. Despite its core influence on ecosystem processes, spatio‐temporal patterns in woodiness remain poorly understood. Here, we aim to demonstrate the global spatio‐temporal patterns in angiosperm woodiness and their relationship with environmental factors. Location Global. Time period Cenozoic, 66 Ma to present. Major taxa studied Angiosperms. Methods Using newly compiled data on the growth forms and distributions of c . 300,000 angiosperm species and an angiosperm phylogeny, we mapped the current global geographical patterns in angiosperm woodiness, reconstructed ancestral states of growth forms through the angiosperm phylogeny and demonstrated the Cenozoic evolutionary dynamics of woodiness. We evaluated the relationships between woodiness and current climate and palaeoclimate. Results We found that c . 42.7% of angiosperms are woody. Woodiness decreased spatially from the equator towards high latitudes, temporally since the early Cenozoic. Temperature was the best predictor of the spatio‐temporal decline in woodiness and was positively correlated with woodiness. Despite the temporal decline in woodiness, macroevolutionary herbaceous‐to‐woody transitions increased through time and contributed to the evolution of woody floras in temperate drylands, whereas the opposite transitions decreased through time and contributed to herbaceous floras in tropical and subtropical drylands. Main conclusions Our study improves understanding of the spatio‐temporal dynamics of angiosperm woodiness. Our findings suggest that temperature is likely to be a determinant of spatio‐temporal variations in woodiness, highlighting the role of temperature in maintaining the growth form composition of ecosystems. Our study also calls for attention to growth form transitions (e.g., secondary woodiness) in temperate drylands that have been neglected before.

How Comamonas testosteroni and Rhodococcus ruber enhance nitrification in the presence of quinoline - Ge Zhu; Haiyun Zhang; Ru Yuan; Meng Huang; Fei Liu; Mo Li; Yongming Zhang; Bruce E. Rittmann (Water Research, 2023)

Multi-stage planning of LID-GREI urban drainage systems in response to land-use changes - Yu Zhang; Mo Wang; Dongqing Zhang; Zhongming Lu; Amin E. Bakhshipour; Ming Liu; Zhiyu Jiang; Jianjun Li; Soon Keat Tan (Science of The Total Environment, 2023)

Calcification of cell membranes: From ions to minerals - Xiao Gao; Jie Li; Kaiming Hu; Yanyang Zhao; Yu Han; Fang Liu; Maurice E. Tucker; Zuozhen Han (Chemical Geology, 2023)

Oxidative stress induced by plasma-activated water stimulates astaxanthin production in Phaffia rhodozyma - Wenshao Li; Carlos H. Luna-Flores; Raveendra Anangi; Renwu Zhou; Xinle Tan; Marius Jessen; Lian Liu; Rusen Zhou; Tianqi Zhang; Alexander Gissibl; Patrick J. Cullen; Kostya (Ken) Ostrikov; et al. (Bioresource Technology, 2023)

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

Implicit satiety goals and food-related expectations predict portion size in older adults: Findings from the BAMMBE cohort - Aimee E. Pink; Li Ling Lee; Dorrain Yanwen Low; Yifan Yang; LaiGuan Zoey Fong; Alicia Yi Hui Kang; Peijia Liu; Hyejin Kim; Yulan Wang; Parasuraman Padmanabhan; Lynne Cobiac; Balázs Gulyás; et al. (Appetite, 2023)

In situ formed CaSO4 on waste dander biochar to inhibit the mineralization of soil organic carbon - Cheng Ji; Shuyi Yang; Ying Cheng; Lin Liu; Daohan Wang; Shujing Zhu; Tao E; Yun Li (Science of The Total Environment, 2023)

Toughing epoxy nanocomposites with graphene-encapsulated liquid metal framework - Da Li; E Peng; Fei Lu; Baolong Wang; Yibo Shen; Pengxiang Liu; Li Liu; Yudong Huang; Zhen Hu (Chemical Engineering Journal, 2023)